Side-to-side differences in lower extremity biomechanics during multi-directional jump landing in volleyball athletes - Sinsurin, K.; Srisangboriboon, S.; Vachalathiti, R. (European Journal of Sport Science, 2017)
Side-to-side differences of lower extremities may influence the likelihood of injury. Moreover, adding the complexity of jump-landing direction would help to explain lower extremity control during sport activities. The aim was to determine the effects of limb dominance and jump-landing direction on lower extremity biomechanics. Nineteen female volleyball athletes participated. Both dominant limbs (DLs) and non-dominant limbs (NLs) were examined in single-leg jump-landing tests in four directions, including forward (0°), diagonal (30° and 60°), and lateral (90°) directions. Kinematic marker trajectories and ground reaction forces were collected using a 10 camera Vicon system and an AMTI force plate. Repeated measures ANOVA (2 × 4, limb × direction) was used to analyse. The finding showed that, at peak vertical GRF, a significant interaction of limb dominance and direction effects was found in the hip flexion angle and lower extremity joint kinetics (p < .05). NLs and DLs exhibited significantly different strategies while landing in various directions. Significantly higher increase of ankle dorsiflexion angle was observed in lateral direction compared to other directions for both DLs and NLs (p < .05). Increasingly using ankle dorsiflexion was observed from the forward to the lateral direction for both DLs and NLs. However, NLs and DLs preferentially used different strategies of joint moment organization to respond to similar VGRFs in various directions. The response pattern of DLs might not be effective and may expose DLs to a higher injury risk, especially with regard to landing with awkward posture compared with NLs.